Image 1_L-shaped association of triglyceride glucose-body mass index and self-rated mental health among the middle-aged and older adults: a national cohort study in China.tiff - Yanqin Li (499034) (2025)
Background Previous studies have shown that the triglyceride glucose-body mass index (TyG-BMI) is associated with cardiovascular disease, stroke, and cognition. Its relationship with mental health remains underexplored. We aimed to investigate the association between TyG-BMI and mental health in Chinese adults. Methods This study utilized data from the China Health and Nutrition Survey (CHNS), an ongoing longitudinal cohort. Participants aged ≥45 years who completed at least two survey rounds between 2009 and 2015 were included. The TyG index was calculated as ln [triglycerides (mg/dL) × fasting blood glucose (mg/dL) / 2]. BMI was calculated as weight (kg) divided by height squared (m2). The TyG-BMI was the product of the TyG index and BMI. Self-rated mental health was assessed using a composite score based on three CHNS questions regarding vitality, happiness, and optimism. Restricted cubic spline (RCS) curves and two-piecewise multivariable Cox hazard regression models, which were adjusted for sociodemographic, lifestyle, and cardiometabolic factors, were employed to explore the relationship between the TyG-BMI and self-rated mental health. Models were adjusted for sociodemographic, lifestyle, and cardiometabolic factors. Results Among 2,951 participants (47.6% male, median age 56.0 [25th, 75th percentile: 51, 64] years), the median TyG-BMI was 204.3 [25th, 75th percentile: 179.6, 231.8]. Over a median follow-up of 6.0 [2.0, 6.1] years, 1,026 (34.8%) incident was identified poor self-rated mental health. RCS curves indicated an L-shaped association between TyG-BMI and self-rated mental health (p for non-linear = 0.033), with an inflection point of 204.3. Below this threshold, each 10-unit increase in TyG-BMI was associated with a 6% decrease in self-rated mental health risk (adjusted hazard ratio [aHR] = 0.94, 95% confidence interval [CI]: 0.90–0.99). Each 1-standard deviation (SD) increase corresponded to a 20% risk reduction (aHR = 0.80, 95% CI: 0.67–0.96). Above the threshold, no significant association was observed. Subgroup and sensitivity analyses yielded consistent results. Conclusion This study revealed an L-shaped association between TyG-BMI and self-rated mental health in mentally healthy, middle-aged and older Chinese individuals. Our findings suggest that TyG-BMI may serve as an effective tool for enhancing the primary prevention of mental health.